Using a space-for-time approach to select the best biodiversity-based indicators to assess the effects of aridity on Mediterranean drylands - Frasconi Wendt, Clara (2020)
Mediterranean drylands are particularly vulnerable to predicted increases in aridity which are expected to have negative consequences for biodiversity. To understand the effects of climate change on ecosystems, a framework for the selection of indicators based on the essential biodiversity variables (EBV) was proposed. In this framework, a functional approach has been suggested because functional traits have shown to be sensitive to small-scale environmental changes. Additionally, functional traits are also associated with ecosystem-limiting processes. In this context, we used ants as ecological indicators, as they are functionally important and respond in a measurable way to environmental changes. We identify which biodiversity-based indicators (e.g., taxonomic, single-trait and multi-trait indices) help track changes in Mediterranean drylands; for this, we used a space-for-time substitution climatic gradient in the western Mediterranean. Ants were sampled along an aridity gradient and identified to species level. Four continuous and seven categorical traits were measured or retrieved from literature. Continuous traits included Weber’s length, which is indicative for body length, head length, eye length and femur length; categorical traits were diet, behavioral dominance, daily activity, nest preference, mound presence, worker polymorphism and foraging strategy. We calculated taxonomic, functional structure and single- and multi-trait functional diversity indices and correlated them with aridity. We found that ant taxonomic and multi-trait functional diversity were maintained along the aridity gradient. Despite maintenance of species and functional diversity along the gradient, ant functional structure responded to aridity with increases in mean trait values of Weber’s length, eye length and femur length in the drier part of the gradient. Under wetter conditions, we found the highest proportion of ants with a seed-based diet, reflecting a potential increase in resource quantity. We observed a change in foraging strategy from group to individual as aridity increased. In conclusion, with a space-for-time substitution climatic gradient, this study shows the potential role of aridity as an environmental driver of ant trait values. These results highlight the value of ants and functional traits as indicators to track the effects of climate change on ecosystems. Finally, this study represents a starting point to monitor important species traits in the context of EBV and to use them as indicators to track the effects of aridity on Mediterranean dryland ecosystems.